The Role of the Community in Efforts to Reduce the Prevalence of Stunting in Kembang Village, Pacitan Regency, East Java - Rizal Al Hamid*; Muhammad Fathun Niam (Universitas Lancang Kuning, 2023)
The stunting prevalence rate in Pacitan still stands at 22.77 per cent. Of course, this figure is still relatively high, far from the target from WHO, below 20 per cent. This fact has encouraged the Kembang Village, Pacitan Regency community to carry out activities or efforts to reduce the prevalence of stunting. First, the form of activities is holding a stunting prevention seminar, where competent speakers such as Ir. Kuriyah, M.M as a representative of PPKB and P3A, then Khuzaini from the Health Office and Yuli Rahmawati Mutiah, M.A from the University Of Warith Al Anbiya. It was second, conducting counselling on stunting in pregnant and lactating women by involving Village Midwives, Posyandu Cadres, and Doctors from Pacitan Health Center. Third, providing balanced and nutritious supplementary food and then distributing the results of processed healthy food to children from the Kembang Village community. The efforts made went well and smoothly. It's due to the support of various parties who participated in the activities' success, especially the people of Kembang Village.